Porównanie zasobów materii organicznej oraz wybranych wskaźników stanu ekochemicznego gleb w zespołach Empetro nigri-Pinetum i Vaccinio uliginosi-Betuletum pubescentis Słowińskiego Parku Narodowego - Jonczak, Jerzy; Parzych, Agnieszka (Leśne Prace Badawcze, 2015)
We conducted comparative studies on soil organic matter stocks and indices of the soil’s ecochemical state under Empetro nigri-Pinetum (En-P) and Vaccinio uliginosi-Betuletum pubescentis (Vu-Bp) in the Słowiński National Park. The investigated plant communities are associated with Arenosols that developed from eolian sands and are exposed to high groundwater levels. The presence of fossil Histosol at a depth of 75 cm in the Vu-Bp stand, which lies below the current groundwater level, is the factor that sets both stands apart. The fossil soil strongly differs from Arenosol in terms of its chemical composition. A high abundance of nutrients in bioavailable forms in the soil is one of the reasons for natural renewal of downy birch in the stand, which presence in turn affects the turnover of elements and the properties of Arenosol. The results of our studies confirm the existence of strong feedback between the soil and plant communities. Soils under the mixed pine-birch Vu-Bp stand are characterized by smaller stocks of organic matter and total organic carbon (TOC) contained in the ectohumus as compared to the soils under the pure pine En-P stand. The opposite is found in the humic horizon. Additionally, in the Vu-Bp stand we observed greater accumulation of total nitrogen (TN) in ectohumus, which is reflected in lower TOC:TN ratios. The contents of TN and TOC:TN ratios in humic horizons were similar in both stands. The soils under En-P were more strongly acidified, especially in O-horizons. Mineral horizons in both stands were characterized by a very small sorptive capacity, which increased in ectohumus and fossil soil. Significant differences between the stands were observed in the ionic composition of sorptive complexes. The soils under Vu-Bp stand were more strongly saturated with basic cations, predominantly calcium. In soil solums of both stands, we observed a deficit of bioavailable potassium and magnesium, which was partially compensated by significant amounts of these components in ectohumus and fossil soil in the Vu-Bp stand. Despite a strongly acidic pH, molar Ca:Al ratios suggest that there are no phytotoxic effects due to free aluminium in ectohumus, while they are unlikely in mineral horizons. The risk of phytotoxic effects is reduced by the influx of calcium from groundwater.